2012
DOI: 10.1021/jp305386e
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Template Rigidity and Amino Acid Type on Heterogeneous Calcium-Phosphate Mineralization by Langmuir Films of Amphiphilic and Acidic β-Sheet Peptides

Abstract: Calcium-phosphate mineralization was monitored in systems composed of designed amphiphilic and acidic β-sheet-forming peptides, namely Pro-Phe-(Asp-Phe)(5)-Pro (PFD-5), Pro-Phe-(Glu-Phe)(5)-Pro (PFE-5) and Pro-Glu-(Phe-PSer)(4)-Phe-Glu-Pro (PPS). The three peptides differ solely in terms of their hydrophilic amino acids and therefore, serve as good model for assessment of the effect of the anionic amino acid type on mineralization within the context of the β-sheet structure. Monolayers of the peptides were dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…This difference in behavior agrees with the observations of Segman-Magidovich and Rapaport, 23 where Brewster angle microscopy (BAM) images showed that Asp-containing peptides adsorbed more ions in the mineralizing solution, a process which was relatively slow for Glu-containing peptides. They also hypothesized that flexible ProAsp-n templates may interact more favorably with Ca 2+ /PO 4 3− clusters.…”
Section: Langmuirsupporting
confidence: 90%
See 1 more Smart Citation
“…This difference in behavior agrees with the observations of Segman-Magidovich and Rapaport, 23 where Brewster angle microscopy (BAM) images showed that Asp-containing peptides adsorbed more ions in the mineralizing solution, a process which was relatively slow for Glu-containing peptides. They also hypothesized that flexible ProAsp-n templates may interact more favorably with Ca 2+ /PO 4 3− clusters.…”
Section: Langmuirsupporting
confidence: 90%
“…The structuring processes of these prenucleation clusters to arrive at amorphous calcium phosphate phases, which later undergo a transition to the stable mineral phase, are still very much under investigation. Segman-Magidovich and Rapaport 23 conducted experiments to examine the effects of different anionic side chains in peptide templates on the early stages of calcium phosphate mineralization. According to their results, it was hypothesized that peptide aggregates with Asp side chains are held together by weaker intermolecular forces, such that the adsorbed ions lead to the disruption of the aggregates.…”
Section: Langmuirmentioning
confidence: 99%
“…Interestingly, positively charged, 59,66-69 ampholytic, 70 or betainic 60,61,71 additives for calcium phosphate mineralization are much less common, despite the fact that such polymers show bactericidal [72][73][74] and antifouling [75][76][77] properties that should also be interesting for dental applications. Additionally, these polymers are able to interact with solids.…”
Section: Introductionmentioning
confidence: 99%
“…Peptide self-association at the air/water interface has been employed for scaffold formation for templated biomineralization, in food processing applications, and to design supramolecular assemblies and nanostructured surfaces. ,, Moreover, the air/water interface has been proposed as a model hydrophobic interface analogous to the membrane aqueous surface . Compression of peptide and protein monolayers has been used to probe the different stages of protein folding , and to mimic the macromolecular crowding conditions of different cell compartments .…”
Section: Introductionmentioning
confidence: 99%